Effect of GnRH on the day of Insemination on Ovulatory Response in Crossbred Cows - Satheshkumar, Soundarapandian; Janani, Prabaharan Yuvan; Praksh, Subramanian; Raja, Sengodan; Jayaganthan , Ponnusamy; Arunmozhi , Narayanasamy (The Indian Journal of Animal Reproduction, 2023)
The effect of gonadotropin releasing hormone (GnRH) analogue on the ovulatory response of oestrual follicle during cold and hotter months of the year was studied. A total of 120 crossbred cows brought for insemination with oestrus signs during colder months (December 2022 –January 2023; n=52) and hotter months (April – May 2023; n=68) to the Gynaecology Unit of Veterinary Clinical Complex, Veterinary College and Research Institute, Orathanadu were utilized for the study. Oestrus (Day 0) was confirmed by gynaeco-clinical and ultrasound examination and animals were inseminated with (n =33) or without (n = 87) GnRH (Buserelin acetate 10 mcg; im). The biometry of oestrual follicle (OF) and regressing corpus luteum (RCL) were measured ultrasonographically on Day 0 and the OF was observed every 24 hours until ovulation. The diameter of the OF on Day 0 was non-significantly (P > 0.05) larger during hotter months (12.19 ± 0.21 mm) than colder months (11.58 ± 0.32 mm).  There were no significant (P > 0.05) differences in the diameter of RCL between the two periods (9.63 ± 0.21 and 9.56 ± 0.22 mm respectively). OFs were observed majorly in the right ovary during the hotter (60.76%) and colder (54.17%) months. Ovulations occurred on the mean days of 1.00 and 1.37 ± 0.18 in GnRH group during hotter (H-Gn) and colder months (C-Gn) respectively. The respective mean days in non-GnRH group were 1.14 ± 0.05 and 1.33 ± 0.08 during hotter (H-O) and colder months (C-O). In H-Gn group all the animals (100%) ovulated on Day 1, when compared to C-Gn animals (62.50%). On perusing the possible effect of RCL on ovulation, significantly increased percentages of ovulations were observed in OFs on the contralateral ovary to the ovary having the RCL in GnRH group and viceversa in non-GnRH group. It could be assumed that GnRH administration on the day of insemination may be beneficial during the hotter months of the year.
Keywords: Crossbred cattle; Insemination; GnRH; Ovulation; Season